Nutritional growth and extraction of poinsettia in response to the ratio nitrate:calcium and phenological stage - Torres-Olivar, Vicente; Villegas-Torres, Oscar Gabriel; Valdez-Aguilar, Luis Alonso; Alia-Tejacal Irán; Sainz-Aispuro Manuel de Jesús; Hernández-Pérez Armando (Revista Mexicana de Ciencias Agrícolas, 2018)
The nutrient requirements of the plants are different in their different phenological stages, so in the present experiment the Steiner solution was modified to adapt it to each stage of poinsettia (root growth, vegetative development and pigmentation). The Prestige cultivar was used the substrate was a mixture of leaf soil, coconut fiber and red tezontle in proportion 60:20:20 (%, v/v) and black polyethylene container of 15.24 cm in diameter. The experiment was carried out in the Faculty of Agricultural Sciences of the Autonomous University of the State of Morelos, Cuernavaca, Morelos. Morphological variables of the poinsettia plants were evaluated in response to the relative concentration between NO3- and Ca2+ of the nutrient solution. The supply of nutrients according to the phenological stages of poinsettia affects the growth, extraction and concentration of nutrients, but depends on the nutritional regime. The regimen with the concentration (in meq L-1) NO3-:Ca2+ 10:7 in radical growth, 10:9 in vegetative development and 12:9 in the pigmentation stage induced the poinsettias to present greater extraction of N, P, K, Ca and Mg, will increase the concentration of K and the morphological characteristics and the production of dry matter were outstanding.